63 Translational Research Capacity in Canadian Pediatric Emergency Departments Participating in the Precision Medicine for Improving the Diagnosis of Pediatric Appendicitis in the Emergency Department (PRIMED) Study. (21st October 2022) - Mitevska, Elena; Mickiewicz, Beata; Thompson, Graham
Abstract: Background: Pediatric clinical and translational research are essential to acquire effective diagnostic and treatment options for children, but they are underfunded and under prioritized in comparison to research focused on treatments for adults. The Precision Medicine for Improving the Diagnosis of Pediatric Appendicitis in the Emergency Department (PRIMED) study aimed to characterize the proteomic and metabolic bio-profiles of children with appendicitis and to investigate these bio-profiles as a clinical prediction tool. Objectives: In this current work, we aimed to evaluate translational research capacity at Canadian pediatric Emergency Departments (EDs) and to describe some of the challenges experienced in the implementation of the PRIMED study and various strategies used to improve local research capacity. Design/Methods: Participating sites provided basic demographic and administrative data along with laboratory- and human-resource availability during enrolment for the PRIMED study. Data was summarized using descriptive statistics. Eleven pediatric EDs participated in the PRIMED study. Results: Six study hospitals (54.5%) used on-site clinical laboratories to process research samples; the remaining hospitals (5/11, 45.5%) required access to research facilities, of which two (18.2%) were off-site. Fewer than two thirds of the study sites (7/11, 63.6%) had any laboratory that would process samples 24 hours per day. Four study sites (36.4%) only enrolled patients during business hours and over half of the sites (6/11, 54.5%) were unable to collect samples for the entire 17:00 to 21:00 peak when the greatest number of pediatric patients present to the ED (Figure 1). There was no nighttime coverage for patient enrollment and sample collection and only three study sites (3/11, 27.3%) had enrollment hours that captured over 75% of the potential study participants. Over half (6/11, 54.5%) of the PRIMED study sites developed novel processes to enable study success, for example creating graduate student on-call schedules and hiring bioscience trained site coordinators to perform sample processing requirements. Conclusion: Despite site-specific efforts to overcome resource barriers, the gap in translational research capacity at academic pediatric emergency departments remains a significant concern. University research institutes and pediatric hospitals should invest in infrastructure and human resources to increase after-hours clinical and translational research capacity to optimize child health and wellness outcomes.